Electromagnetic modeling of a reconfigurable graphene-based metasurface using MoM-GEC method for 3D digital holography. Issue 13 (2nd September 2019) - Soltani, Imen; Soltani, Takoua; Aguili, Taoufik
ABSTRACT: Viewing the trend of beam shaping, beam steering, and metasurface holograms, a reconfigurable graphene-based metasurface is proposed and modeled using the method of moments combined with the generalized equivalent circuit (MoM-GEC) approach. The scattering state of each individual unit cell of the metasurface can be controlled by applying different biased voltages into the graphene antennas. In fact, the complex surface conductivity of graphene is introduced in our mathematical formulation in order to tune the magnitude and phase of the local reflection coefficient. Benefitting from this scalability, our graphene-based metasurface will regenerate a 3D medical hologram. The proposed approach is validated and paves the way for the generation a 3D digital holograms. There are several important areas where this study makes an original contribution such as medical imaging 3D displays.